Elements of banking - Whiting, D. P. (Plymouth : Macdonald and Evans, 1979)
This Handbook provides a basic knowledge of the British banking system. It examines the place of banks within the national economy and outlines banking operations and services.
Includes index.
Keywords: Banks and banking